Pediatric near-drownings: clinical insights and prediction of life-threatening events - Sharif, Asmaa F.; Alwarhi, Mohammed S.; Alshamrani, Abdulaziz S.; Alharbi, Adel O.; Alwayil, Nasser M.; Alharbi, Turki N.; Alsarhan, Abdulwahab S.; Alghamdi, Abdulrhman S. (Frontiers in Pediatrics, 2026)
IntroductionDrowning is a leading cause of mortality in children worldwide. Near-drowning is a state of survival after asphyxia due to submersion in water. Drowning-related incidents have significantly increased in developed countries. Even survivors suffer from various long-lasting morbidities. Early prediction of mortality and morbidly life-threatening events is life-saving and guides decision-making in such critical situations. This study aimed to identify early predictors of mortality and other unfavorable outcomes (hypoxic brain injury and respiratory failure necessitating mechanical ventilation) in children diagnosed with near-drowning.MethodsThis retrospective cross-sectional study enrolled 247 children who nearly drowned and were admitted to National Guard Hospitals, Saudi Arabia, between 2,015 and 2024. The studied patients were categorized into two groups: patients with favorable outcomes and those with unfavorable outcomes. The all-subset regression method was employed to identify the best predictors for the investigated outcomes.ResultsThe death rate and incidence of brain insults constituted 15% each, while 25% of the investigated patients were complicated by respiratory failure. Most admissions (60%) occurred in the summer, and 86% of drownings occurred at swimming pools. Death was significantly associated with greater prehospital delay (time from exposure until arrival at emergency services) (p < 0.05). A proposed model that exhibited a performance of 92% identified the Glasgow Coma Scale score on admission as a significant predictor of brain insults. Significant predictors of mortality included lower bicarbonate levels [adjusted odds ratio (OR) = 0.598, p < 0.001], higher sodium levels (adjusted OR = 1.802, p < 0.001), lower chloride levels (adjusted OR = 0.721, p = 0.008), and greater red cell distribution width (adjusted OR = 2.158, p = 0.009).ConclusionThis study identified several available laboratory markers as early predictors of mortality in pediatric near-drowning patients. These markers help to identify patients at increased risk of life-threatening events when combined with established clinical predictors. This study emphasized the critical roles of prehospital factors, initial clinical presentation, and physiological derangements in pediatric near-drowning patients. The observed findings highlight possible areas accessible for public health interventions, including intensifying preventive measures at night, in the summer, and in swimming pools. Offering optimum on-scene resuscitation and rapid hospital transfer are other recommended actions expected to be associated with fewer adverse events.